PENGARUH LATIHAN DRILL RECEIVE PASSING BAWAH SASARAN TETAP TERHADAP KEMAMPUAN MENGARAHKAN BOLA VOLI KE PEMAIN POSISI SETTER - Amin Dananjaya; Setya Rahayu (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA (UTP), 2026)
The sport of volleyball places the setter position player as the main organizer of the attack. The success of the attack is greatly influenced by the quality of the receive from the opponent's serve which is then directed to the setter. This study aims to analyze the effect of drill receive lower passing with a fixed target on the technical ability and accuracy of directing the ball to the setter position player. Quasi-experimental method with one group pretest-posttest design. The subjects were 21 male volleyball players aged 14-16 years from Club Trisula Berlian Semarang. The research instrument was a test of technique and accuracy of receiving lower passing with a setter target. The results of the research on the drill practice of receiving lower passes with a fixed target on the ability to receive technique value x ? pretest 16.76 post test 22.47, t count 9.749> t table 2.093 and sig.? 0.00. Accuracy of receive directing the ball x ? pre test 3.90 post test 6.52, t count 9.775 > t table 2.093 and sig.? 0.00. It can be concluded that the practice of drill receive lower passing has a significant effect on improving the ability of technique and accuracy of receive lower passing.